Gene markers for exon capture and phylogenomics in ray‐finned fishes. Issue 7 (5th March 2019) - Jiang, Jiamei; Yuan, Hao; Zheng, Xin; Wang, Qian; Kuang, Ting; Li, Jingyan; Liu, Junning; Song, Shuli; Wang, Weicai; Cheng, Fangyuan; Li, Hongjie; Huang, Junman; et al.
Abstract: Gene capture coupled with the next‐generation sequencing has become one of the preferred methods of subsampling genomes for phylogenomic studies. Many exon markers have been developed in plants, sharks, frogs, reptiles, fishes, and others, but no universal exon markers have been tested in ray‐finned fishes. Here, we identified a suite of "single‐copy" protein‐coding sequence (CDS) markers through comparing eight fish genomes, and tested them empirically in 83 species (33 families and nine orders or higher clades: Acipenseriformes, Lepisosteiformes, Elopomorpha, Osteoglossomorpha, Clupeiformes, Cypriniformes, Gobiaria, Carangaria, and Eupercaria; sensu Betancur et al. 2013). Sorting the markers according to their completeness and phylogenetic decisiveness in taxa tested resulted in a selection of 4, 434 markers, which were proven to be useful in reconstructing phylogenies of the ray‐finned fishes at different taxonomic levels. We also proposed a strategy of refining baits (probes) design a posteriori based on empirical data. The markers that we have developed may greatly enrich the batteries of exon markers for phylogenomic study in ray‐finned fishes. Abstract : The identification of exons and target enrichment experiments collecting these exons from the genomes of ray‐finned fishes for the purpose of phylogenetic inference was described. Empirical tests were performed across several different clades of ray‐finned fish to show that the bait set is universal and informative at different timescales.